New binaries among UV-selected, hot subdwarf stars and population properties - Kawka, Adela; Vennes, S.; O'Toole, S.; Németh, P.; Burton, D.; Kotze, E.; Buckley, D. (Oxford University Press, 2015)
We have measured the orbital parameters of seven close binaries, including six new objects, in a radial velocity survey of 38 objects comprising a hot subdwarf star with orbital periods ranging from ~0.17 to 3 d. One new system, GALEX J2205-3141, shows reflection on an M dwarf companion. Three other objects show significant short-period variations, but their orbital parameters could not be constrained. Two systems comprising a hot subdwarf paired with a bright main-sequence/giant companion display short-period photometric variations possibly due to irradiation or stellar activity and are also short-period candidates. All except two candidates were drawn from a selection of subluminous stars in the Galaxy Evolution Explorer ultraviolet sky survey. Our new identifications also include a low-mass subdwarf B star and likely progenitor of a low-mass white dwarf (GALEX J0805-1058) paired with an unseen, possibly substellar, companion. The mass functions of the newly identified binaries imply minimum secondary masses ranging from 0.03 to 0.39M?. Photometric time series suggest that, apart from GALEX J0805-1058 and J2205-3141, the companions are most likely white dwarfs. We update the binary population statistics: close to 40 per cent of hot subdwarfs have a companion. Also, we found that the secondary mass distribution shows a lowmass peak attributed to late-type dwarfs, and a higher mass peak and tail distribution attributed to white dwarfs and a few spectroscopic composites. Also, we found that the population kinematics imply an old age and include a few likely halo population members.